1969
DOI: 10.1172/jci106035
|View full text |Cite
|
Sign up to set email alerts
|

Influence of the thyroid state on left ventricular tension-velocity relations in the intact, sedated dog

Abstract: The mechanical properties of left ventricular contraction were described in terms of tension, velocity, length, and time in closed-chest, sedated normal, hypothyroid, and hyperthyroid dogs. Heart rate was controlled at 150 beats/min, and instantaneous contractile element velocity was calculated from left ventricular pressure and its first derivative during isovolumic left ventricular contractions, produced by sudden balloon occlusion of the ascending aorta during diastole. Wall tension was derived from ventric… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
29
0
1

Year Published

1977
1977
2012
2012

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 108 publications
(31 citation statements)
references
References 40 publications
1
29
0
1
Order By: Relevance
“…Similar studies on the force-frequency relationship were made by Murayama and Goodkind (1968) in the guinea pig, and again it was observed that the changes were independent of norepinephrine stores. Taylor et al (1969) obtained CIRCULATION RESEARCH VOL. 44, No.…”
Section: Effects Of Thyrotoxicosis On Myocardialmentioning
confidence: 99%
See 1 more Smart Citation
“…Similar studies on the force-frequency relationship were made by Murayama and Goodkind (1968) in the guinea pig, and again it was observed that the changes were independent of norepinephrine stores. Taylor et al (1969) obtained CIRCULATION RESEARCH VOL. 44, No.…”
Section: Effects Of Thyrotoxicosis On Myocardialmentioning
confidence: 99%
“…absolute heart weight usually is normal or only slightly increased in chronic experiments on animals (Taylor et al, 1969) and in man with uncomplicated thyroid hyperfunction (Friedberg and Sohval, 1937). Nevertheless, the speed of contraction is increased and the time of tension development is shortened in both early (Buccino et al, 1967;Pannier, 1968;Korecky and Beznak, 1971;Murayama and Goodkind, 1968) and well established thyrotoxicosis (Taylor et al, 1969;Amidi et al, 1968;Grossman et al, 1971). Clinical experience suggests that cardiac function may be maintained at above normal levels for many years, unless there is advanced age or coincident cardiac disease (Hurxthal, 1940;Sandier and Wilson, 1959).…”
Section: Effects Of Thyrotoxicosis On Myocardialmentioning
confidence: 99%
“…In this study, the severity of reduced thyroid hormone may have masked a potentially beneficial influence that might have been present with less severe interruption of normal metabolism. The absence of a reduction in first derivative of left ventricular pressure (dPldt) rise, plausibly viewed as one index of contractility is, on first appearance, inconsistent with in vitro studies which have shown a reduction in contractile function of hypothyroid papillary muscle (49), or studies in lightly anesthetized hypothyroid dogs which have shown a displacement of the tension-velocity relationship of the left ventricle (50). In vitro studies are devoid of neural and humoral regulation, and we suspect that the absence of reduced contractility in this conscious canine model may be due to supportive neural and humoral reflexes known to be initiated by reduction in mean systemic pressure.…”
Section: Discussionmentioning
confidence: 97%
“…Noninvasive evaluation of myocardial function, both in animals and humans, has shown opposite abnormalities in systolic time intervals in primary hypothyroidism and hyperthyroidism that can be reversed by appropriate therapy (7,8,9). In primary hypothyroidism, systolic time intervals are typically lengthened and decreased after T 4 replacement in correlation with changes in thyroid hormones (10).…”
Section: Introductionmentioning
confidence: 99%